Advancement in thermophotovoltaic technology and nanoparticle incorporation for power generation - Khairul Azri A.A.; Mohd Jasni M.S.; Wan Muhamad Hatta S.F.; Islam M.A.; Abdul Wahab Y.; Mekhilef S.; Ker P.J. (Elsevier Ltd, 2024)
Thermophotovoltaic (TPV) technology harvests electricity from a source of thermal radiation and at current, TPV cells can achieve conversion efficiency of more than 40%. The construct of the TPV system is relatively complex than the conventional solar cell in which the TPV has two critical components, specifically the absorber-emitter and filters, to help in enhancing the transfer of photons to the TPV cell for conversion. Despite its importance, works on the optimization of these components for an ideal TPV system are still lacking. This review examines previous studies on the TPV structure, and details extensive techniques to improve current designs of the TPV systems - notably through the use of textured absorbers, selective emitters and different types of filters. Inevitably, the selection of materials and designs of the absorber-emitter are essential in enhancing the TPV performance. Herein, challenges and enhancements in the form of optical performance, thermal stability, and electrical performance are comprehensively discussed. This review identifies the crucial role of nanoparticles incorporated into the absorber-emitter layer of a TPV system. This review also critically highlights technology advancements incorporated into the TPV technology which will effectively boost performance and improve the fabrication and operational costs of this sustainable technology. 2023 International Solar Energy Society